Nistisima : the secret to delicious vegan cooking from the Mediterranean and beyond - Hayden, Georgina (Bloomsbury Publishing, 2022)
"No fads, no frills, just 120 vegan recipes that have stood the test of time from award-winning food writer Georgina Hayden, currently appearing on Channel 4's The Great Cookbook Challenge. Nistisima means fasting food - food eaten during Lent and other times of fasting observed by those of Orthodox faith. Mostly this involves giving up meat and dairy and instead using vegetables, pulses and grains to create easy, delicious dishes that all just happen to be vegan. In this book, Georgina draws on the history and culture around nistisimo cooking in the Mediterranean, Middle East and Eastern Europe to share the simple, nutritious and flavour-packed recipes at the heart of the practice, including: Salatet malfouf cabbage slaw; Briam ('Greek ratatouille'); Pumpkin, raisin and harissa pie; Kibbet el raheb, 'monks' soup'; Jewelled lentil moutzentra; Rizogalo rose rice pudding with roasted strawberries; Moustokouloura spiced grape, honey and chocolate biscuits. Whether you're vegan, vegetarian, or simply want to eat more plant-based food, Nistisima offers you tried and tested recipes that celebrate the very best of this tradition - all bursting with flavour and all surprisingly vegan"--Publisher's description.